ChemInform Abstract: Supported Ionic Liquids: Efficient and Reusable Green Media in Organic Catalytic Chemistry. Issue 14 (March 2016) - Xin, Bingwei; Jia, Chunxiao; Li, Xinmin
Abstract: Review: 139 refs.